Influence of doping on crystal growth, structure and optical properties of nanocrystalline CaTiO3: a case study using small‐angle neutron scattering. (1st June 2015) - Mondal, Oindrila; Pal, Manisha; Singh, Ripandeep; Sen, Debasis; Mazumder, Subhasish; Pal, Mrinal
<x xml:space="preserve">Abstract</x> The effect of dopant size (ionic radius) on the crystal growth, structure and optical properties of nanocrystalline calcium titanate, CaTiO3 (CTO), have been studied using small‐angle neutron scattering. X‐ray diffraction, along with high‐resolution transmission electron microscopy, confirms the growth of pure nanocrystalline CTO. Rietveld analysis reveals that the difference of ionic radii between dopant and host ions induces strain within the lattice, which significantly affects the lattice parameters. The induced strain, due to the difference of ionic radii, causes the shrinkage of the optical band gap, which is manifested by the redshift of the absorbance band. Mesoscopic structural analysis using scattering techniques demonstrates that the ionic radius of the dopant influences the agglomeration behaviour and particle size. A high‐resolution transmission electron microscopy study reconfirms the formation of pure highly crystalline CTO nanoparticles.